PERANAN KONSULTAN HAK KEKAYAAN INTELEKTUAL DALAM PERLINDUNGAN HAK KEKAYAAN INTELEKTUAL BERDASARKAN PERATURAN PEMERINTAH NO 2 TAHUN 2005 - , Shitavadani Devi, SH., MKn; , Irna Nurhayati, S.H., M.Hum., LL.M. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research on The Role Of The Consultant Of Intellectual Property Rights In Intellectual Property Rights Protection Based On Indonesian Government Regulation Number 2 Year 2005 was an empirical legal research to obtain primary data. But to support and complete this research, it also conduct normative legal research that is based on library research to obtain secondary data in the field of law. Implementation goal of this research is to investigate about the role of the Consultant of Intellectual Property Rights in Intellectual Property Rights protection based on Indonesian Government Regulation Number 2 Year 2005 and to know about constraints faced by the consultant of intellectual property rights in carrying out their role. Data collected will then be analyzed using qualitative methods, which is, a method by describing and linking between one data with the other data as a whole, so that it will obtain a clear description of the answer to the formulation of existing problems. After analyzing the data, the result showed that the role of the Consultant of Intellectual Property Rights in Intellectual Property Rights protection based on Indonesian Government Regulation Number 2 Year 2005 is sufficient where the Consultant of Intellectual Property Rights to helping people to be more understand about intellectual property rights and to understand the importance of intellectual property rights protection by carry out their duties and obligation in helping represent the registration of intellectual property rights and to provide extensive information related to the knowledge of intellectual property rights. As for the obstacles encountered by the consultant of intellectual property rights in carrying out their role are the unhealthy competition among fellow consultant of intellectual property rights, lack of efficient management of intellectual property rights registration in the office of Directorate General of Intellectual Property Rights, not many people know the consultant of intellectual property rights profession, and lack of appreciation for this profession so that people still consider this profession as a regular service bureau. This constraints complicate the consultant of intellectual property rights in carrying out their roles that related to intellectual property rights protection.